Improved Aerosol Processes and Effective Radiative Forcing in HadGEM3 and UKESM1. (10th November 2018) - Mulcahy, J. P.; Jones, C.; Sellar, A.; Johnson, B.; Boutle, I. A.; Jones, A.; Andrews, T.; Rumbold, S. T.; Mollard, J.; Bellouin, N.; Johnson, C. E.; Williams, K. D.; et al.
Abstract: Aerosol processes and, in particular, aerosol‐cloud interactions cut across the traditional physical‐Earth system boundary of coupled Earth system models and remain one of the key uncertainties in estimating anthropogenic radiative forcing of climate. Here we calculate the historical aerosol effective radiative forcing (ERF) in the HadGEM3‐GA7 climate model in order to assess the suitability of this model for inclusion in the UK Earth system model, UKESM1. The aerosol ERF, calculated for the year 2000 relative to 1850, is large and negative in the standard GA7 model leading to an unrealistic negative total anthropogenic forcing over the twentieth century. We show how underlying assumptions and missing processes in both the physical model and aerosol parameterizations lead to this large aerosol ERF. A number of model improvements are investigated to assess their impact on the aerosol ERF. These include an improved representation of cloud droplet spectral dispersion, updates to the aerosol activation scheme, and black carbon optical properties. One of the largest contributors to the aerosol forcing uncertainty is insufficient knowledge of the preindustrial aerosol climate. We evaluate the contribution of uncertainties in the natural marine emissions of dimethyl sulfide and organic aerosol to the ERF. The combination of model improvements derived from these studies weakens the aerosol ERF by up to 50% of the original value and leads to a total anthropogenic historical forcing more in line with assessed values. Key Points: The HadGEM3‐GA7 climate model has a large, negative aerosol ERF resulting in an unrealistic negative total anthropogenic forcing of climate The aerosol ERF is shown to be highly sensitive to the underlying physical and aerosol model processes and parameterizations Through a combination of scientific model improvements the aerosol ERF is reduced by up to 50% from –2.75 to –1.45 W/m 2